An Investigation of Cryptojacking: Malware Analysis and Defense Strategies - Marchetto, Victor; Liu, Xiang (Journal of Strategic Innovation and Sustainability, 2019)
Cybercriminals are capitalizing on the global interest in speculative cryptocurrencies for their own gain. By exploiting vulnerabilities in web browsers and client systems on a large scale, such new operating model named as cryptojacking allows cybercriminals to siphon computational resources from their victims to illicitly generate cryptocurrency. The authors analyze cryptojacking malware samples using both static and dynamic methods and discuss their potential impacts on services running on enterprise servers and operating systems including critical infrastructure industries. The paper further provides strategies for how to detect and defend against these threats.